Cerebellum and Prematurity: A Complex Interplay Between Disruptive and Dysmaturational Events - Spoto, Giulia; Amore, Greta; Vetri, Luigi; Quatrosi, Giuseppe; Cafeo, Anna; Gitto, Eloisa; Nicotera, Antonio Gennaro; Di Rosa, Gabriella (Frontiers in Systems Neuroscience, 2021)
The cerebellum plays a critical regulatory role in motor coordination, cognition, behavior, language, memory, and learning, hence overseeing a multiplicity of functions. Cerebellar development begins during early embryonic development, lasting until the first postnatal years. Particularly, the greatest increase of its volume occurs during the third trimester of pregnancy, which represents a critical period for cerebellar maturation. Preterm birth and all the related prenatal and perinatal contingencies may determine both dysmaturative and lesional events, potentially involving the developing cerebellum, and contributing to the constellation of the neuropsychiatric outcomes with several implications in setting-up clinical follow-up and early intervention.